1984
DOI: 10.1002/ajp.1350060305
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and physiological suppression of fertility in subordinate marmoset monkeys

Abstract: In laboratory groups of common marmosets (Callithrix jacchus jacchus), socially induced reproductive suppression among subordinates and offspring effectively maintained a monogamous breeding system. Male subordinates or male offspring were inhibited or restrained from showing sexual behavior, while similarly placed females could also suffer from complete ovarian failure. In well-established families, a familiarity or inbreeding taboo restricted reproduction among otherwise fertile offspring. However, only one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
247
0
7

Year Published

1994
1994
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 298 publications
(267 citation statements)
references
References 34 publications
13
247
0
7
Order By: Relevance
“…In addition, an age-related dominance hierarchy is often apparent, either within each sex or in both sexes combined (Sutcliffe & Poole 1984;Digby 1995b). Both males and females may be highly aggressive to unfamiliar or extragroup individuals of the same sex, but within established groups, aggression is usually mild and infrequent (Epple 1967;Abbott 1984;Saltzman et al 1994Saltzman et al , 1997cDigby 1995b;Sousa et al 2005).…”
Section: Marmoset Social and Breeding Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, an age-related dominance hierarchy is often apparent, either within each sex or in both sexes combined (Sutcliffe & Poole 1984;Digby 1995b). Both males and females may be highly aggressive to unfamiliar or extragroup individuals of the same sex, but within established groups, aggression is usually mild and infrequent (Epple 1967;Abbott 1984;Saltzman et al 1994Saltzman et al , 1997cDigby 1995b;Sousa et al 2005).…”
Section: Marmoset Social and Breeding Systemsmentioning
confidence: 99%
“…Reproductive skew in female marmosets W. Saltzman et al 391 (Rothe 1975;Abbott 1984;Saltzman et al 1997c) and in the field (Digby 1999;Sousa et al 2005). Several investigators have, on rare occasions, observed dominant females disrupting subordinate females' sexual interactions with males (Epple 1967;Rothe 1975;Abbott 1984 Abbott 1999, unpublished data) and, in the laboratory groups, most subordinate females are never seen even attempting to mate (Rothe 1975;Abbott 1984). Thus, interference by dominant females is unlikely to be a primary cause of sexual inhibition in subordinates.…”
Section: What Are the Proximate Mechanisms Inhibiting Sexual Behavioumentioning
confidence: 99%
“…The vomeronasal organ (VNO) is thought to be related to the reproductive and social behaviors by perceiving pheromonal molecules to send olfactory information to the accessory olfactory bulb [1,8,11,22,31]. Phylogenetically, the VNO first appears in amphibians, is well developed in reptiles, but absent in birds [4,11,13,14].…”
mentioning
confidence: 99%
“…Due to intense reproductive competition in the species, the dominance relationship among females has been very well studied. However, documentation about escape from inhibition by subordinate calli-thrichid females in laboratory groups (among mothers and daughters or among unrelated females) has shown that reproductive inhibition is not as stringent as thought (7)(8)(9)(10)(11). The escape from inhibition by subordinate females (daughters) was also recorded in a monogamous wild group of common marmosets (12).…”
Section: Introductionmentioning
confidence: 98%